Gita: The Essence of Life - Sharada, Gangotri; Ghodake, Ganesh (International Journal of Psychosocial Rehabilitation, 2020)
The Bhagavad Gita forms a section of the sixth book of the Mahabharata, an important Sanskrit epic in the Hindu tradition that recounts a lengthy struggle and brief war between two sides of the Bharata family the Pandavas and the Kaurvas over their kingdom of Hastinapura. The Gita recounts a dialogue in the moments leading up to the war between the Pandava warrior Arjuna and his charioteer and trusted advisor, Krishna, who turns out to be a worldly incarnation of Vishnu, a god who serves as the Supreme Being in many forms of Hinduism. However, Arjuna and Krishna’s dialogue is actually recounted through a frame story: Sanjaya, an advisor to Dhritarashtra (the Kauravas’ father and the blind king of Hastinapura), and reports this dialogue to the king after the Pandavas have already won the war.